Carbon nanotubes and carbon nanoonions inhibit the formation of amyloid fibrils from whey protein isolate - Lisha Wang; Ning Kang; Hu Shi; Lizhen Gao (Carbon Trends)
To investigate the impact of carbon nanomaterials on whey protein isolate (WPI), composites of carbon nanotubes (CNTs) and carbon nanonions (CNOs) with WPI were synthesized. The structures and interactions of these composites were characterized using techniques such as TEM, SEM, FTIR, and XRD. Upon combining CNTs and CNOs with WPI, it was observed that WPI did not form fibers but instead wrapped around the carbon nanomaterials, causing agglomeration. Compared with WPI/CNTs composites, WPI/CNOs exhibited higher stability. SEM images and XRD diffraction peaks both indicated that CNTs were completely wrapped by WPI, while CNOs were not fully wrapped, with some parts exposed on the protein surface. Molecular dynamics simulations (MDs) revealed that double-walled carbon nanoonions (C60@C240) reduced the β-sheet and α-helix content of β-lactoglobulin (β-lg), while double-walled carbon nanotubes (DWCNT) increased the α-helical protein content. Both types of carbon nanomaterials inhibited the conformational changes of β-lg protein associated with the formation of amyloid fibrils. The fluctuations in the internal hydrogen bond interactions of β-lg protein in the three systems indicated that the secondary structure of β-lg protein had indeed changed after its interaction with carbon nanomaterials. CNOs formed stronger interactions with WPI, resulting in greater stability of the CNOs/WPI composite. This study elucidated the inhibitory effect of CNTs and CNOs on the fibril formation of WPI, which may hold significant implications for the application of nanocarbon and protein composites.